The role of insulin resistance in the development of muscle wasting during cancer cachexia - Honors, Mary A.; Kinzig, Kimberly P. (Journal of cachexia, sarcopenia and muscle, 2012)
Background Cancer cachexia is a complex syndrome associated with multiple metabolic abnormalities. Insulin resistance is present in many cancer patients and may be one mechanism through which muscle wasting occurs. Methods and results The present review examines evidence in support of a role for insulin resistance in the development of muscle wasting during cancer cachexia and identifies areas for future research. Patients suffering from cancer cachexia tend to exhibit insulin resistance and improvements in insulin resistance have the potential to improve cachexia symptoms. In addition, evidence suggests that insulin resistance may occur prior to the onset of cachexia symptoms. Conclusions Further investigation of the role of insulin resistance in cancer cachexia is needed. The use of translational research in this area is strongly encouraged, and has important implications for clinical research and the treatment and prevention of cancer cachexia.